Multinationals from the third World - "Lall, Rajiv B." (Delhi, 1986)
India is perhaps the only developing country whose direct investments overseas exceed investments by other countries within it. Dr Lall examines information collected through interviews with a number of Indian firms with manufacturing operations abroad, to provide the basis for, and to supplement, a more general statistical analysis.
Keywords: International business enterprises developing countries